Pengaruh Pembangunan Di Pemukiman Pesisir Pantai Di Kelurahan Oesapa Terhadap Rencana Tata Ruang Kota Kupang - Denny Ebenhaizer Laiskodat; Benediktus Peter Lay; Maria Kartika Mao Foju (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The 1945 Constitution, article 33 paragraph 3, mandates that the land, water and natural resources contained therein are controlled by the State and used as much as possible for the prosperity of the people. Soil is a natural resource gifted by God Almighty that cannot be separated from the order of human life, according to the Big Indonesian Dictionary (1991), soil is the surface of the earth or the layers of the earth above it; the state of the earth somewhere; circumscribed earth conditions. Land in the juridical sense is the surface of the earth (UUPA paragraph 1). While land rights are the rights of certain parts of the earth's surface which are limited, have two dimensions in length and width. The transfer of land rights causes the land rights to be transferred from one person to another. Legal acts of transferring land rights can be carried out by buying and selling, exchanging, grants or grants by testament. All the realities that give rise to social conflict and that occur a lot are suspected to be the result of imbalances in land administration processes, land law enforcement, weak government spatial planning policies, and so on. The distribution of settlements in the Oesapa Village is divided into 3 (three) areas, namely the coast, land and hills. The rate of arrival (urbanization) for students, especially tertiary institutions, causes an increase in the need for housing. This situation has resulted in an increase in the use of space in the city of Kupang to support the activities and movements of the increasing population, causing the need for land as a place to construct buildings to become very difficult to obtain, this affects the availability of settlements that can be said to be healthy. The research method used is descriptive, normative, and quantitative. This is intended so that in the preparation, data collection, and data processing stages, quality data is obtained that supports the objectives of this study.